Interactional metadiscourse in academic research article abstracts as marker of discipline - Khedri, Mohsen; Tan, Bee Hoon; Chan, Swee Heng (Academy of Language Studies, Universiti Teknologi MARA, 2012)
Research article abstracts as a communicative genre let readers know the significant features of the research. In this regard, they are considered powerful to inform the scientific community of new findings. This study explores the status of interactional metadiscourse markers in research article abstracts across disciplines. The purpose is to investigate how these cohesive devices are manifested and tackled by research article writers in their abstracts in the effort to reach the audience so as to create interpersonality in discourse. Hyland’s (2005) taxonomy of metadiscourse was adopted to analyze sixty research article abstracts written in two disciplines (Applied Linguistics and Economics) selected from related journals. Results indicated that variations were present across two disciplines regarding interactional metadiscourse markers, especially attitude markers and self-mentions. Results of the present research may have some implications for novice researchers of the identified fields in meeting the needs of expertise and in getting an entry into their own disciplinary community.